(untitled) (Revista Brasileira Multidisciplinar, 2025)
The hypopressive abdominal gymnastics technique comprises exercises that generate a decrease in abdominal and thoracic pressure, combining controlled methods and abdominal traction maneuvers, reflexively activating the abdominal and pelvic floor muscles. It can treat various dysfunctions related to the lumbopelvic region, such as urinary incontinence, diastasis of the rectus abdominis muscles and low back pain. The objective was to carry out an integrative review on the effects of hypopressive gymnastics on urinary incontinence, diastasis of the rectus abdominis muscles and low back pain. An integrative review was performed using the following databases: PubMed, Scielo, Lilacs and PeDro, using the keywords in English and Portuguese: urinary incontinence, low back pain, hypopressive abdominal gymnastic, hypopressive method and diastasis of the rectus abdominis, grouping the studies in a table composed by: authors/year, type of study, objective of the study, sample, intervention and result. Nine studies were analyzed and selected that brought hypopressive abdominal gymnastics as a possibility of treatments in rectus abdominis diastasis, urinary incontinence and low back pain, as well as its effects on these. It is concluded at the end of this study that hypopressive abdominal gymnastics can be used in the disorders listed here, as it has beneficial effects for these, mainly in the reduction of abdominal diastasis, symptoms of urinary incontinence and improvement of muscle dysfunction, reducing low back pain and improving its functionality and mobility. However, it is still necessary that new studies be carried out, since the literature is still scarce to approach this subject.